(3JUMja GdeMOKjfs - (3GdMSf Hf YHO Gddg Hf SYjO Hf ESeGYjd GdnYrSncQj, CHh CMeO,J (B382 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi SGHZ aVdg hLRjd UfYg MeOkG jhLH QVG s
(3ef cJH GdYdGeI GdTfbjWis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B196s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B94 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eUWdM(B) s
Keywords: (3GdJGQjNs